Cytogenetics of Channa pulchra Britz, 2007 - Muayprom, Tanada Raiwin; Tanomtong, Alongklod; Supiwong, Weerayuth (KKU Science Journal, 2024)
The first cytogenetics of Burmese peacock snakehead fish (Channa pulchra Britz, 2007) in Salween river was investigated in this study. Mitotic chromosome was directly prepared from kidney of 5 male and 5 female specimens after in vivo colchicine treatment. Conventional staining and NOR banding technique were performed for the studies of chromosome type and number, and NORs bearing chromosome. The results showed that the diploid number (2n) was 48 and fundamental number (NF) was 94 in both male and female. The types of chromosomes were 16 large metacentric, 22 large submetacentric, 2 medium metacentric, 6 medium submetacentric, and 2 small telocentric chromosomes. The karyotypes are not different of sex chromosomes between male and female. The karyotype formula for the eye-spotted barb is as follows: 2n (48) = Lm16 + Lsm22 + Mm2 + Msm6 + St2. The chromosome pairs 14 had NORs location adjacent to submetacentric chromosome in the telomere position of the short arm. These results will be useful for providing basic genetics information and future studies of breeding, conservation and chromosome evolution in this animal.